Super-hydrophobic wear-resistant aluminum alloy material and preparation method thereof
By setting a gradient ceramic film coated with alumina on the surface of the aluminum alloy and performing laser pulse treatment, the corrosion and wear of aluminum alloy materials in harsh environments is solved, and higher hydrophobicity and wear resistance are achieved.
Patent Information
- Application Number
- CN202411584352.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-21
AI Technical Summary
Existing aluminum alloy materials are prone to corrosion and wear in wet, corrosive environments or in high friction scenarios, resulting in insufficient service life and performance.
By setting a gradient ceramic film coated with alumina on the surface of the aluminum alloy, combined with laser pulse treatment, the hydrophobicity and wear resistance of the material are improved.
It significantly improves the hydrophobicity and wear resistance of aluminum alloy materials, extends service life, and shows better performance under harsh working conditions.
Smart Images

Figure BDA0005123937970000101 
Figure BDA0005123937970000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of aluminum alloy materials, and in particular to a super hydrophobic and wear-resistant aluminum alloy material and a preparation method thereof. Background Art
[0002] Aluminum alloys have been widely used in aerospace, automobile manufacturing, construction and many other fields due to their excellent properties such as low density and high specific strength. However, in some special environments, such as humid, corrosive environments or high friction scenarios, ordinary aluminum alloys face corrosion and wear problems. The research on super hydrophobic and wear-resistant aluminum alloy materials aims to solve these problems and improve the service life and performance of aluminum alloys under harsh working conditions. Through chemical etching, anodizing and other methods, microscopic rough structures, such as nano-scale protrusions and holes, can be constructed on the surface of aluminum alloys. These microstructures are similar to the papillary structures on the surface of lotus leaves, which can effectively capture air and thus improve the hydrophobicity of the surface. For example, the roughness of the microstructure of the aluminum alloy surface prepared by chemical etching increases, which reduces the contact area between the water droplet and the material surface and increases the contact angle. On the basis of constructing the microstructure, a material with low surface energy, such as fluorocarbon polymers, is coated. This coating can further reduce the surface energy, making it easier for water droplets to roll on the surface without wetting. Studies have found that the synergistic effect of the fluorocarbon coating and the microstructure can make the contact angle of the aluminum alloy surface reach more than 150°, achieving super hydrophobic properties. Adding an appropriate amount of alloying elements, such as copper, magnesium, zinc, etc., to aluminum alloys can form a strengthening phase and improve the hardness and wear resistance of the material. For example, the second phase particles in the Al-Cu-Mg aluminum alloy can hinder the movement of dislocations, thereby improving the wear resistance of the material. In addition to constructing the microstructure and coating of the super-hydrophobic surface, the wear resistance of aluminum alloys can also be improved by using methods such as ion implantation and laser surface treatment. Ion implantation can form a hardened layer on the surface of aluminum alloys, and laser surface treatment can change the organizational structure of the material surface. Both can effectively reduce wear. As research continues to deepen, the performance of super-hydrophobic and wear-resistant aluminum alloy materials needs to be further improved. In the future, they may be used in more fields, such as marine engineering and electronic equipment housings. At the same time, it is also necessary to explore more environmentally friendly and low-cost preparation methods to promote their large-scale industrial production. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a super hydrophobic and wear-resistant aluminum alloy material, which can improve the hydrophobicity and wear resistance of the aluminum alloy material through the surface enhancement effect of the gradient ceramic film coated with alumina.
[0004] Technical solution: A super hydrophobic and wear-resistant aluminum alloy material, the aluminum alloy material includes an aluminum alloy base material and an alumina-coated gradient ceramic film, the alumina-coated gradient ceramic film includes an alumina-coated low-porosity ceramic film and an alumina-coated high-porosity ceramic film, the alumina-coated low-porosity ceramic film is located on the surface of the aluminum alloy material, and the aluminum alloy base material is composed of the following components in weight percentage: Si 0.05-0.1wt% Fe 0.08-0.15wt% Cu 2-2.5wt% Mn 0.01-0.04wt% Cr 0.01-0.14wt% Mg 1.8-2.2wt% Zn 6-8wt% Ti 0.02-0.05wt% Al is the balance. Preferably, the method for preparing the alumina-coated gradient ceramic membrane comprises the following steps: S11. PVP, PSN and CTAB are added to anhydrous ethanol, and stirred to mix well to obtain a precursor A solution; S12. PVP, PSN and CTAB are added to anhydrous ethanol, stirred and mixed, castor oil is added, and the mixture is stirred and mixed to obtain a precursor B solution; S13. Electrospinning the precursor A solution prepared in step S1 to obtain an electrospinning membrane A, and then compounding the precursor B solution prepared in step S2 on the surface of the electrospinning membrane A to obtain an electrospinning membrane B to obtain a composite electrospinning membrane; S14. Sintering the spinning membrane to obtain a gradient ceramic membrane; S15. Aluminum nitrate is added to water and stirred until dissolved, and then a polyethylene glycol solution is added dropwise and mixed to obtain a mixed solution, the gradient ceramic membrane prepared in step S4 is added to the mixed solution, and then ammonium bicarbonate is added, and after the solution is ultrasonically treated to make it gel-like, the surface-modified gradient ceramic membrane is removed by suction; S16. Dry and sinter the surface-modified gradient ceramic membrane prepared in step S5 to obtain an alumina-coated gradient ceramic membrane. The preparation method of the above-mentioned super-hydrophobic wear-resistant ceramic aluminum alloy material comprises the following steps: S1. Mixing and melting the aluminum alloy matrix material; S2. placing the gradient ceramic film coated with alumina at the bottom of the mold, pouring the molten aluminum alloy matrix material into the mold, and sintering to obtain an aluminum-based composite material; S3. The aluminum-based composite material is subjected to a solution and artificial aging heat treatment. The aluminum-based composite material is first placed in a muffle furnace and heated to 550-560°C, and kept at this temperature for 30 minutes at a heating rate of 8-10°C / min. After being taken out, it is air-cooled. Then, the sample is placed in a tubular furnace and heated to 180-200°C, and kept at this temperature for 450-500 minutes at a heating rate of 8-10°C / min. After being taken out, it is air-cooled. S4. The treated aluminum-based composite material is subjected to laser pulse treatment with a pulse energy density of 80-120 J / cm 2 , pulse width is 30-50ns, argon gas pressure is 0.1-0.5Mpa, and super hydrophobic and wear-resistant aluminum alloy material is obtained. Preferably, the sintering process in step S2 is: first sintering at 300°C for 10 minutes with a sintering pressure of 4-5Mpa, then heating to 550-660°C at a rate of 2-3°C / min, keeping warm for 10 minutes, with a sintering pressure of 10-13Mpa. Preferably, the mass ratio of PVP, polysilazane, CTAB and anhydrous ethanol in step S11 and step S12 is 1-1.5:2.5-3.5:8-10:0.2-0.3; the content of castor oil in S12 accounts for 10-20wt% of the precursor B solution. Preferably, in step S13, the porosity of the electrospinning membrane A is 85-95%, and the thickness thereof is 100-200 um, and the porosity of the electrospinning membrane B is 50-70%, and the thickness thereof is 100-200 um. Preferably, in step S14, the sintering is performed by heating the temperature to 1350-1450° C. at a rate of 5-10° C. / min and keeping the temperature for 1-1.5 h. Preferably, the molar ratio of aluminum nitrate to ammonium bicarbonate in step S15 is 1:3. Preferably, in step S16, the sintering is performed by heating the temperature to 840-880° C. at a rate of 3-5° C. / min, and the holding time is 1-1.5 h. Beneficial effects: The super hydrophobic and wear-resistant ceramic aluminum alloy material of the present invention has the following advantages: 1. In the present invention, a ceramic film with a gradient change is provided on the surface of the aluminum alloy. The ceramic film is composed of a composite of a high-porosity and a low-porosity ceramic film. The low-porosity ceramic film is a SiC ceramic film with a mesoporous structure, and the surface is loaded with nano-alumina. The high-porosity ceramic is a common alumina-coated SiC ceramic film. The mesoporous SiC ceramic film can further increase the micro-nano effect of the ceramic film surface, thereby improving the wear resistance of the aluminum alloy. The high-porosity ceramic film can further strengthen the bonding effect between the ceramic film and the aluminum alloy substrate. 2. In order to further improve the hydrophobic effect and wear resistance, the present invention uses a gradient ceramic membrane combined with laser pulse processing to further expose the micro-nano structure of the ceramic membrane, while further increasing the surface roughness to improve the hydrophobic effect; 3. The alumina layer coated on the surface of the ceramic film in the present invention helps the whiskers to combine with the aluminum alloy matrix during the sintering process, plays the role of the gradient ceramic film in bearing the load in the matrix, and inhibits the slip deformation of the soft Al matrix to a certain extent, which is manifested in the macroscopic aspect of improving the hardness of the composite material. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 The method for preparing the gradient ceramic membrane coated with alumina comprises the following steps: S11. PVP, PSN and CTAB were added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol was 1.5:3.5:10:0.3, and the mixture was stirred to obtain a precursor A solution; S12. PVP, PSN and CTAB are added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol is 1.5:3.5:10:0.3, and the mixture is stirred and mixed evenly, and castor oil is added, and the mixture is stirred and mixed evenly to obtain a precursor B solution, wherein the content of castor oil accounts for 12wt% of the precursor B solution; S13. The precursor A solution prepared in step S11 is first electrospun to obtain an electrospinning membrane A, wherein the porosity of the electrospinning membrane A is 88.9% and the thickness is 165 μm. Then, the precursor B solution prepared in step S12 is used to prepare an electrospinning membrane B on the surface of the electrospinning membrane A, wherein the porosity of the electrospinning membrane B is 62.3% and the thickness is 141 μm, thereby obtaining a composite electrospinning membrane; S14. Sintering the spun membrane, raising the temperature to 1350° C. at 5° C. / min, and keeping the temperature for 1 h to obtain a gradient ceramic membrane; S15. Aluminum nitrate is added to water and stirred until dissolved, and then a polyethylene glycol solution is added dropwise and mixed to obtain a mixed solution, the gradient ceramic membrane prepared in step S14 is added to the mixed solution, and then ammonium bicarbonate is added, the molar ratio of aluminum nitrate to ammonium bicarbonate is 1:3, ultrasonic treatment is performed to make the solution gel-like, and then the surface-modified gradient ceramic membrane is removed by suction; S16. The surface-modified gradient ceramic membrane prepared in step S15 is dried and then sintered, and the temperature is increased to 840° C. at a rate of 3° C. / min and kept at the temperature for 1 hour to obtain an alumina-coated gradient ceramic membrane. Example 2 The method for preparing the gradient ceramic membrane coated with alumina comprises the following steps: S11. PVP, PSN and CTAB were added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol was 1:2.5:8:0.2, and the mixture was stirred to obtain a precursor A solution; S12. PVP, PSN and CTAB are added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol is 1.5:3.5:10:0.3, and the mixture is stirred and mixed evenly, and castor oil is added, and the mixture is stirred and mixed evenly to obtain a precursor B solution, wherein the content of castor oil accounts for 10wt% of the precursor B solution; S13. The precursor A solution prepared in step S11 is first electrospun to obtain an electrospinning membrane A, wherein the porosity of the electrospinning membrane A is 86.9% and the thickness is 145 μm. Then, the precursor B solution prepared in step S12 is composited on the surface of the electrospinning membrane A to obtain an electrospinning membrane B, wherein the porosity of the electrospinning membrane B is 55.6% and the thickness is 168 μm, thereby obtaining a composite electrospinning membrane; S14. Sintering the spun membrane, heating to 1450°C at 10°C / min, and keeping the temperature for 1.5h to obtain a gradient ceramic membrane; S15. Aluminum nitrate is added to water and stirred until dissolved, and then a polyethylene glycol solution is added dropwise and mixed to obtain a mixed solution, the gradient ceramic membrane prepared in step S14 is added to the mixed solution, and then ammonium bicarbonate is added, the molar ratio of aluminum nitrate to ammonium bicarbonate is 1:3, ultrasonic treatment is performed to make the solution gel-like, and then the surface-modified gradient ceramic membrane is removed by suction; S16. The surface-modified gradient ceramic membrane prepared in step S15 is dried and then sintered, and the temperature is increased to 880° C. at a rate of 5° C. / min and the heat preservation time is 1.5 h to obtain an alumina-coated gradient ceramic membrane. Example 3 The method for preparing the gradient ceramic membrane coated with alumina comprises the following steps: S11. PVP, PSN and CTAB were added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol was 1.2:2.8:8:0.2, and the mixture was stirred to obtain a precursor A solution; S12. PVP, PSN and CTAB are added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol is 1.2:2.8:8:0.2, and the mixture is stirred and mixed evenly, and castor oil is added, and the mixture is stirred and mixed evenly to obtain a precursor B solution, wherein the content of castor oil accounts for 13wt% of the precursor B solution; S13. The precursor A solution prepared in step S11 is first electrospun to obtain an electrospun membrane A, the porosity of the electrospun membrane A is 90.2%, and the thickness is 135 um. Then, the precursor B solution prepared in step S12 is used to composite an electrospun membrane B on the surface of the electrospun membrane A, the porosity of the electrospun membrane B is 55.9%, and the thickness is 170 um, to obtain a composite electrospun membrane; S14. Sintering the spun membrane, raising the temperature to 1380°C at 8°C / min, and keeping the temperature for 1h to obtain a gradient ceramic membrane; S15. Aluminum nitrate is added to water and stirred until dissolved, and then a polyethylene glycol solution is added dropwise and mixed to obtain a mixed solution, the gradient ceramic membrane prepared in step S14 is added to the mixed solution, and then ammonium bicarbonate is added, the molar ratio of aluminum nitrate to ammonium bicarbonate is 1:3, ultrasonic treatment is performed to make the solution gel-like, and then the surface-modified gradient ceramic membrane is removed by suction; S16. The surface-modified gradient ceramic membrane prepared in step S15 is dried and then sintered, and the temperature is increased to 860° C. at a rate of 3° C. / min and kept at the temperature for 1 hour to obtain an alumina-coated gradient ceramic membrane. Example 4 The method for preparing the gradient ceramic membrane coated with alumina comprises the following steps: S11. PVP, PSN and CTAB were added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol was 1.4:3.2:10:0.4, and the mixture was stirred to obtain a precursor A solution; S12. PVP, PSN and CTAB are added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol is 1.4:3.2:10:0.4, and the mixture is stirred and mixed evenly, and castor oil is added, and the mixture is stirred and mixed evenly to obtain a precursor B solution, wherein the content of castor oil accounts for 17wt% of the precursor B solution; S13. The precursor A solution prepared in step S11 is first electrospun to obtain an electrospun membrane A, the porosity of the electrospun membrane A is 92.3%, and the thickness is 154 um. Then, the precursor B solution prepared in step S12 is used to composite an electrospun membrane B on the surface of the electrospun membrane A, the porosity of the electrospun membrane B is 61.4%, and the thickness is 158 um, to obtain a composite electrospun membrane; S14. Sintering the spun membrane, heating to 1430°C at 10°C / min, and keeping the temperature for 1.5h to obtain a gradient ceramic membrane; S15. Aluminum nitrate is added to water and stirred until dissolved, and then a polyethylene glycol solution is added dropwise and mixed to obtain a mixed solution, the gradient ceramic membrane prepared in step S14 is added to the mixed solution, and then ammonium bicarbonate is added, the molar ratio of aluminum nitrate to ammonium bicarbonate is 1:3, ultrasonic treatment is performed to make the solution gel-like, and then the surface-modified gradient ceramic membrane is removed by suction; S16. The surface-modified gradient ceramic membrane prepared in step S15 is dried and then sintered, and the temperature is increased to 870° C. at a rate of 5° C. / min and kept at this temperature for 1.5 h to obtain an alumina-coated gradient ceramic membrane. Example 5 A super hydrophobic wear-resistant aluminum alloy material, the aluminum alloy material comprises an aluminum alloy base material and an aluminum oxide-coated gradient ceramic film, the aluminum oxide-coated gradient ceramic film comprises an aluminum oxide-coated low-porosity ceramic film and an aluminum oxide-coated high-porosity ceramic film, the aluminum oxide-coated low-porosity ceramic film is located on the surface of the aluminum alloy material, and the aluminum alloy base material is composed of the following components in weight percentage: Si is 0.05wt%, Fe is 0.15wt%, Cu is 2.5wt%, Mn is 0.04wt%, Cr is 0.01wt%, Mg is 1.8wt%, Zn is 6wt%, Ti is 0.05wt%, and Al is the balance; A method for preparing a super hydrophobic wear-resistant ceramic aluminum alloy material, the preparation method comprising the following steps: S1. Mixing and melting the aluminum alloy matrix material; S2. The alumina-coated gradient ceramic membrane prepared in Example 1 is placed at the bottom of the mold, and the low-porosity side of the alumina-coated gradient ceramic membrane is attached to the bottom of the mold. The molten aluminum alloy matrix material is poured into the mold and sintered. The sintering is first carried out at 300°C for 10 minutes at a sintering pressure of 4 MPa, and then the temperature is increased to 550°C at a rate of 2°C / min, and the temperature is kept for 10 minutes at a sintering pressure of 10 MPa to obtain an aluminum-based composite material. S3. The aluminum-based composite material is subjected to solid solution and artificial aging heat treatment. The aluminum-based composite material is first placed in a muffle furnace and heated to 550°C, and kept at this temperature for 30 minutes at a heating rate of 8°C / min. After being taken out, it is air-cooled. Then, the sample is placed in a tubular furnace and heated to 180°C, and kept at this temperature for 450 minutes at a heating rate of 8°C / min. After being taken out, it is air-cooled. S4. The treated aluminum-based composite material is subjected to laser pulse treatment with a pulse energy density of 80 J / cm 2 , pulse width is 30ns, argon pressure is 0.1Mpa, and a super-hydrophobic and wear-resistant aluminum alloy material is obtained. Example 6 A super hydrophobic wear-resistant aluminum alloy material, the aluminum alloy material comprises an aluminum alloy base material and an aluminum oxide-coated gradient ceramic film, the aluminum oxide-coated gradient ceramic film comprises an aluminum oxide-coated low-porosity ceramic film and an aluminum oxide-coated high-porosity ceramic film, the aluminum oxide-coated low-porosity ceramic film is located on the surface of the aluminum alloy material, and the aluminum alloy base material is composed of the following components in weight percentage: Si is 0.1wt%, Fe is 0.08wt%, Cu is 2wt%, Mn is 0.01wt%, Cr is 0.14wt%, Mg is 2.2wt%, Zn is 8wt%, Ti is 0.02wt%, and Al is the balance; A method for preparing a super hydrophobic wear-resistant ceramic aluminum alloy material, the preparation method comprising the following steps: S1. Mixing and melting the aluminum alloy matrix material; S2. The alumina-coated gradient ceramic membrane prepared in Example 2 is placed at the bottom of the mold, and the low-porosity side of the alumina-coated gradient ceramic membrane is attached to the bottom of the mold. The molten aluminum alloy matrix material is poured into the mold and sintered. The sintering is first carried out at 300°C for 10 minutes at a sintering pressure of 5 MPa, and then the temperature is increased to 660°C at a rate of 3°C / min, and the temperature is kept for 10 minutes at a sintering pressure of 13 MPa to obtain an aluminum-based composite material. S3. The aluminum-based composite material is subjected to solid solution and artificial aging heat treatment. The aluminum-based composite material is first placed in a muffle furnace and heated to 560°C, and kept at this temperature for 30 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled. Then, the sample is placed in a tubular furnace and heated to 200°C, and kept at this temperature for 500 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled. S4. The treated aluminum-based composite material is subjected to laser pulse treatment with a pulse energy density of 120 J / cm 2 , pulse width is 50ns, argon pressure is 0.5Mpa, and a super-hydrophobic and wear-resistant aluminum alloy material is obtained. Example 7 A super hydrophobic wear-resistant aluminum alloy material, the aluminum alloy material comprises an aluminum alloy base material and an aluminum oxide-coated gradient ceramic film, the aluminum oxide-coated gradient ceramic film comprises an aluminum oxide-coated low-porosity ceramic film and an aluminum oxide-coated high-porosity ceramic film, the aluminum oxide-coated low-porosity ceramic film is located on the surface of the aluminum alloy material, and the aluminum alloy base material is composed of the following components in weight percentage: Si is 0.09wt%, Fe is 0.1wt%, Cu is 2.2wt%, Mn is 0.02wt%, Cr is 0.05wt%, Mg is 1.9wt%, Zn is 7.5wt%, Ti is 0.03wt%, and Al is the balance; A method for preparing a super hydrophobic wear-resistant ceramic aluminum alloy material, the preparation method comprising the following steps: S1. Mixing and melting the aluminum alloy matrix material; S2. The alumina-coated gradient ceramic membrane prepared in Example 3 is placed at the bottom of the mold, and the low-porosity side of the alumina-coated gradient ceramic membrane is attached to the bottom of the mold. The molten aluminum alloy matrix material is poured into the mold and sintered. The sintering is first carried out at 300°C for 10 minutes at a sintering pressure of 4 MPa, and then the temperature is increased to 640°C at a rate of 3°C / min, and the temperature is kept for 10 minutes at a sintering pressure of 10 MPa to obtain an aluminum-based composite material. S3. The aluminum-based composite material is subjected to solution and artificial aging heat treatment. The aluminum-based composite material is first placed in a muffle furnace and heated to 560°C and kept at this temperature for 30 minutes at a heating rate of 8°C / min. After being taken out, it is air-cooled. Then, the sample is placed in a tubular furnace and heated to 200°C and kept at this temperature for 450 minutes at a heating rate of 8°C / min. After being taken out, it is air-cooled. S4. The treated aluminum-based composite material is subjected to laser pulse treatment with a pulse energy density of 90 J / cm 2 , pulse width is 35ns, argon pressure is 0.2Mpa, and super hydrophobic and wear-resistant aluminum alloy material is obtained. Example 8 A super hydrophobic wear-resistant aluminum alloy material, the aluminum alloy material comprises an aluminum alloy base material and an aluminum oxide-coated gradient ceramic film, the aluminum oxide-coated gradient ceramic film comprises an aluminum oxide-coated low-porosity ceramic film and an aluminum oxide-coated high-porosity ceramic film, the aluminum oxide-coated low-porosity ceramic film is located on the surface of the aluminum alloy material, and the aluminum alloy base material is composed of the following components in weight percentage: Si is 0.06wt%, Fe is 0.13wt%, Cu is 2.4wt%, Mn is 0.03wt%, Cr is 0.1wt%, Mg is 2.1wt%, Zn is 6.5wt%, Ti is 0.04wt%, and Al is the balance; A method for preparing a super hydrophobic wear-resistant ceramic aluminum alloy material, the preparation method comprising the following steps: S1. Mixing and melting the aluminum alloy matrix material; S2. The alumina-coated gradient ceramic membrane prepared in Example 4 is placed at the bottom of the mold, and the low-porosity side of the alumina-coated gradient ceramic membrane is attached to the bottom of the mold. The molten aluminum alloy matrix material is poured into the mold and sintered. The sintering is first carried out at 300°C for 10 minutes at a sintering pressure of 5 MPa, and then the temperature is increased to 580°C at a rate of 2°C / min, and the temperature is kept for 10 minutes at a sintering pressure of 13 MPa to obtain an aluminum-based composite material; S3. The aluminum-based composite material is subjected to a solid solution and artificial aging heat treatment. The aluminum-based composite material is first placed in a muffle furnace and heated to 550°C, and kept at this temperature for 30 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled. Then, the sample is placed in a tubular furnace and heated to 180°C, and kept at this temperature for 500 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled. S4. The treated aluminum-based composite material is subjected to laser pulse treatment with a pulse energy density of 110 J / cm 2 , pulse width is 45ns, argon pressure is 0.4Mpa, and super hydrophobic and wear-resistant aluminum alloy material is obtained. Comparative Example 1 A super hydrophobic wear-resistant aluminum alloy material, the aluminum alloy material comprises an aluminum alloy base material and an aluminum oxide-coated gradient ceramic film, the aluminum oxide-coated gradient ceramic film comprises an aluminum oxide-coated low-porosity ceramic film and an aluminum oxide-coated high-porosity ceramic film, the aluminum oxide-coated low-porosity ceramic film is located on the surface of the aluminum alloy material, and the aluminum alloy base material is composed of the following components in weight percentage: Si is 0.06wt%, Fe is 0.13wt%, Cu is 2.4wt%, Mn is 0.03wt%, Cr is 0.1wt%, Mg is 2.1wt%, Zn is 6.5wt%, Ti is 0.04wt%, and Al is the balance; A method for preparing a super hydrophobic wear-resistant ceramic aluminum alloy material, the preparation method comprising the following steps: S1. Mixing and melting the aluminum alloy matrix material; S2. The alumina-coated gradient ceramic membrane prepared in Example 4 is placed at the bottom of the mold, and the low-porosity side of the alumina-coated gradient ceramic membrane is attached to the bottom of the mold. The molten aluminum alloy matrix material is poured into the mold and sintered. The sintering is first carried out at 300°C for 10 minutes at a sintering pressure of 5 MPa, and then the temperature is increased to 580°C at a rate of 2°C / min, and the temperature is kept for 10 minutes at a sintering pressure of 13 MPa to obtain an aluminum-based composite material; S3. The aluminum-based composite material is subjected to solid solution and artificial aging heat treatment. First, the aluminum-based composite material is placed in a muffle furnace and heated to 550°C, and kept warm for 30 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled. Then, the sample is placed in a tubular furnace and heated to 180°C, and kept warm for 500 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled to obtain a super hydrophobic and wear-resistant aluminum alloy material. Comparative Example 2 A super hydrophobic and wear-resistant aluminum alloy material, comprising an aluminum alloy base material and an aluminum oxide-coated ceramic film, wherein the aluminum alloy base material is composed of the following components in weight percentage: Si is 0.06wt%, Fe is 0.13wt%, Cu is 2.4wt%, Mn is 0.03wt%, Cr is 0.1wt%, Mg is 2.1wt%, Zn is 6.5wt%, Ti is 0.04wt%, and Al is the balance; A method for preparing a super hydrophobic wear-resistant ceramic aluminum alloy material, the preparation method comprising the following steps: S1. Mixing and melting the aluminum alloy matrix material; S2. The prepared alumina-coated gradient ceramic membrane is placed at the bottom of the mold, and the low-porosity side of the alumina-coated gradient ceramic membrane is attached to the bottom of the mold. The molten aluminum alloy matrix material is poured into the mold and sintered. The sintering is first carried out at 300°C for 10 minutes at a sintering pressure of 5 MPa, and then the temperature is increased to 580°C at a rate of 2°C / min, and the temperature is kept for 10 minutes at a sintering pressure of 13 MPa to obtain an aluminum-based composite material; S3. The aluminum-based composite material is subjected to a solid solution and artificial aging heat treatment. The aluminum-based composite material is first placed in a muffle furnace and heated to 550°C, and kept at this temperature for 30 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled. Then, the sample is placed in a tubular furnace and heated to 180°C, and kept at this temperature for 500 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled. S4. The treated aluminum-based composite material is subjected to laser pulse treatment with a pulse energy density of 110 J / cm 2 , the pulse width is 45ns, the argon pressure is 0.4Mpa, and a super-hydrophobic and wear-resistant aluminum alloy material is obtained; The method for preparing the alumina-coated ceramic membrane comprises the following steps: S11. PVP, PSN and CTAB were added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol was 1.4:3.2:10:0.4, and the mixture was stirred to obtain a precursor solution; S12. The precursor solution prepared in step S11 is electrospun to obtain an electrospun membrane, wherein the porosity of the electrospun membrane is 88.5% and the thickness is 310 um; S13. Sintering the spun membrane, heating to 1430°C at 10°C / min, and keeping the temperature for 1.5h to obtain a ceramic membrane; S14. Aluminum nitrate is added to water and stirred until dissolved, and then a polyethylene glycol solution is added dropwise and mixed to obtain a mixed solution, the ceramic membrane prepared in step S13 is added to the mixed solution, and then ammonium bicarbonate is added, the molar ratio of aluminum nitrate to ammonium bicarbonate is 1:3, ultrasonic treatment is performed to make the solution gel-like, and then the surface-modified gradient ceramic membrane is removed by suction; S15. The surface-modified ceramic membrane prepared in step S14 is dried and then sintered, and the temperature is increased to 870°C at a rate of 5°C / min and kept at this temperature for 1.5 hours to obtain an alumina-coated gradient ceramic membrane. Comparative Example 3 A super hydrophobic and wear-resistant aluminum alloy material, the aluminum alloy material comprises an aluminum alloy base material and a gradient ceramic film, the gradient ceramic film comprises a low-porosity ceramic film and a high-porosity ceramic film, the low-porosity ceramic film is located on the surface of the aluminum alloy material, and the aluminum alloy base material is composed of the following components in weight percentage: Si is 0.06wt%, Fe is 0.13wt%, Cu is 2.4wt%, Mn is 0.03wt%, Cr is 0.1wt%, Mg is 2.1wt%, Zn is 6.5wt%, Ti is 0.04wt%, and Al is the balance; A method for preparing a super hydrophobic wear-resistant ceramic aluminum alloy material, the preparation method comprising the following steps: S1. Mixing and melting the aluminum alloy matrix material; S2. The gradient ceramic membrane prepared in Example 4 is placed at the bottom of the mold, and the low porosity side of the gradient ceramic membrane is attached to the bottom of the mold. The molten aluminum alloy matrix material is poured into the mold and sintered. The sintering is first carried out at 300°C for 10 min, and the sintering pressure is 5 MPa. Then, the temperature is increased to 580°C at a rate of 2°C / min, and the temperature is kept for 10 min. The sintering pressure is 13 MPa to obtain an aluminum-based composite material. S3. The aluminum-based composite material is subjected to a solid solution and artificial aging heat treatment. The aluminum-based composite material is first placed in a muffle furnace and heated to 550°C, and kept at this temperature for 30 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled. Then, the sample is placed in a tubular furnace and heated to 180°C, and kept at this temperature for 500 minutes at a heating rate of 10°C / min. After being taken out, it is air-cooled. S4. The treated aluminum-based composite material is subjected to laser pulse treatment with a pulse energy density of 110 J / cm 2 , the pulse width is 45ns, the argon pressure is 0.4Mpa, and a super-hydrophobic and wear-resistant aluminum alloy material is obtained; The preparation method of the gradient ceramic membrane comprises the following steps: S11. PVP, PSN and CTAB were added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol was 1.4:3.2:10:0.4, and the mixture was stirred to obtain a precursor A solution; S12. PVP, PSN and CTAB are added to anhydrous ethanol, the mass ratio of polysilazane, CTAB and anhydrous ethanol is 1.4:3.2:10:0.4, and the mixture is stirred and mixed evenly, and castor oil is added, and the mixture is stirred and mixed evenly to obtain a precursor B solution, wherein the content of castor oil accounts for 17wt% of the precursor B solution; S13. The precursor A solution prepared in step S11 is first electrospun to obtain an electrospun membrane A, the porosity of the electrospun membrane A is 92.3%, and the thickness is 154 um. Then, the precursor B solution prepared in step S12 is used to composite an electrospun membrane B on the surface of the electrospun membrane A, the porosity of the electrospun membrane B is 61.4%, and the thickness is 158 um, to obtain a composite electrospun membrane; S14. Sinter the spun membrane, raise the temperature to 1430°C at a rate of 10°C / min, and keep the temperature for 1.5 hours to obtain a gradient ceramic membrane. Performance test: The contact angle was measured by FTA1000 contact angle meter. The droplet size was about 5μL. Five positions were randomly selected on each sample and the average value of the measured values was taken. The mechanical stability of the superhydrophobic material was tested by a friction test. Cotton cloth was used as the grinding head for the friction test. Under a pressure of 15KPa, one back and forth friction was counted as one time. The distance of one cycle was 6cm. The contact angle of the sample was measured after different times of friction. Unrubbed contact angle / ° Contact angle after 1500 frictions / ° Contact angle after 3000 frictions / ° Example 5 165.5 163.2 158.9 Example 6 163.8 160.2 157.5 Example 7 164.7 162.5 157.8 Example 8 166.2 163.5 159.2 Comparative Example 1 156.9 148.9 140.2 Comparative Example 2 155.6 152.6 147.8 Comparative Example 3 152.9 148.7 140.2 The microhardness of the sample was tested using a semi-automatic digital microhardness tester with a load of 20 g and a load holding time of 20 s. Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A super hydrophobic wear-resistant aluminum alloy material, characterized in that: The aluminum alloy material comprises an aluminum alloy base material and an alumina-coated gradient ceramic film, wherein the alumina-coated gradient ceramic film comprises an alumina-coated low-porosity ceramic film and an alumina-coated high-porosity ceramic film, wherein the alumina-coated low-porosity ceramic film is located on the surface layer of the aluminum alloy material, and the aluminum alloy base material is composed of the following components in weight percentage: Si 0.05-0.1wt% Fe 0.08-0.15wt% Cu 2-2.5wt% Mn 0.01-0.04wt% Cr 0.01-0.14wt% Mg 1.8-2.2wt% Zn 6-8wt% Ti 0.02-0.05wt% Al is the balance.
2. The super hydrophobic wear-resistant aluminum alloy material according to claim 1, characterized in that: The method for preparing the alumina-coated gradient ceramic membrane comprises the following steps: S11. PVP, PSN and CTAB are added to anhydrous ethanol, and stirred to mix well to obtain a precursor A solution; S12. PVP, PSN and CTAB are added to anhydrous ethanol, stirred and mixed, castor oil is added, and the mixture is stirred and mixed to obtain a precursor B solution; S13. The precursor A solution prepared in step S1 is first electrospun to obtain an electrospinning membrane A, and then the precursor B solution prepared in step S2 is composited on the surface of the electrospinning membrane A to obtain an electrospinning membrane B to obtain a composite electrospinning membrane; S14. Sintering the spun membrane to obtain a gradient ceramic membrane; S15. Aluminum nitrate is added to water and stirred until dissolved, and then a polyethylene glycol solution is added dropwise and mixed to obtain a mixed solution, the gradient ceramic membrane prepared in step S4 is added to the mixed solution, and then ammonium bicarbonate is added, and after the solution is ultrasonically treated to make it gel-like, the surface-modified gradient ceramic membrane is removed by suction; S16. Dry and sinter the surface-modified gradient ceramic membrane prepared in step S5 to obtain an alumina-coated gradient ceramic membrane.
3. The method for preparing a super hydrophobic wear-resistant ceramic aluminum alloy material according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Mixing and melting the aluminum alloy matrix material; S2. placing the alumina-coated gradient ceramic film in a mold, pouring the molten aluminum alloy matrix material into the mold, and sintering to obtain an aluminum-based composite material; S3. The aluminum-based composite material is subjected to a solution and artificial aging heat treatment. The aluminum-based composite material is first placed in a muffle furnace and heated to 550-560°C, and kept at this temperature for 30 minutes at a heating rate of 8-10°C / min. After being taken out, it is air-cooled. Then, the sample is placed in a tubular furnace and heated to 180-200°C, and kept at this temperature for 450-500 minutes at a heating rate of 8-10°C / min. After being taken out, it is air-cooled. S4. The treated aluminum-based composite material is subjected to laser pulse treatment with a pulse energy density of 80-120 J / cm 2 , pulse width is 30-50ns, argon gas pressure is 0.1-0.5Mpa, and super hydrophobic and wear-resistant aluminum alloy material is obtained.
4. The method for preparing a super hydrophobic wear-resistant ceramic aluminum alloy material according to claim 3, characterized in that: The sintering process in step S2 is: first sinter at 300°C for 10 minutes with a sintering pressure of 4-5Mpa, then heat to 550-660°C at a rate of 2-3°C / min, keep warm for 10 minutes, and sinter at a sintering pressure of 10-13Mpa.
5. The super hydrophobic and wear-resistant aluminum alloy material according to claim 2, characterized in that: The mass ratio of PVP, polysilazane, CTAB and anhydrous ethanol in step S11 and step S12 is 1-1.5:2.5-3.5:8-10:0.2-0.3; the content of castor oil in S12 accounts for 10-20wt% of the precursor B solution.
6. The super hydrophobic and wear-resistant aluminum alloy material according to claim 2, characterized in that: In the step S13, the porosity of the electrospinning membrane A is 85-95%, and the thickness thereof is 100-200 um, and the porosity of the electrospinning membrane B is 50-70%, and the thickness thereof is 100-200 um.
7. The super hydrophobic and wear-resistant aluminum alloy material according to claim 2, characterized in that: In the step S14, the sintering is performed by heating the temperature to 1350-1450° C. at a rate of 5-10° C. / min and keeping the temperature for 1-1.5 hours.
8. The super hydrophobic and wear-resistant aluminum alloy material according to claim 2, characterized in that: The molar ratio of aluminum nitrate to ammonium bicarbonate in step S15 is 1:
3.
9. The super hydrophobic and wear-resistant aluminum alloy material according to claim 2, characterized in that: In the step S16, the sintering is performed by heating the temperature to 840-880° C. at a rate of 3-5° C. / min, and the holding time is 1-1.5 h.